Imobilização da enzima invertase em material mesoporoso SBA-15 com superfícies funcionalizadas por diferentes compostos orgânicos - Ribeiro , Lívia Maria de Oliveira (2016)
The search for appropriate supports for enzyme immobilization has attracted increasing interest in the field of biocatalysis. Immobilized enzymes are catalysts of enormous industrial interest because they combine the advantages of heterogeneous catalysis with the high selectivity and mild operational conditions of enzymes. In 1998, a new mesoporous material with highly ordered hexagonal structure was developed at the University of Santa Barbara, United States, and called SBA-15. This material has mesopores of about 6.0 nm in diameter, specific surface area of the order of 800 m2/g and, in addition, it has a large amount of free silanol groups (≡Si - OH) present on the pore walls. The presence of these groups allows functionalize its surface, making it more efficient and selective as adsorbing materials. In this work we were synthesized mesoporous molecular sieves SBA-15, which have had their surfaces modified by various organic molecules, such as trimethoxyphenylsilane (TMOS), vinyltrimethoxysilane (VMOS) and γ - minopropyltriethoxysilane (APTES). The synthesized samples were characterized by spectroscopy in the infrared (FT-IR), thermal analysis (TG / DTG), nitrogen adsorption (BET) and scanning electron microscopy (SEM). The mesoporous molecular sieves SBA-15 after functionalization, were used for the immobilization of invertase diameter of approximately 4.5 nm. We evaluated the performance of immobilization for each employee support and the best results of immobilization yield in the range of 80% were achieved using the support functionalized with silane agent APTES due to greater anchoring enzymes on its surface. These results indicate functionalization as a promising alternative to applying the support in obtaining immobilized biocatalyst.